Bies na dnie butelki… Myśli i konteksty do relektury poematu Jerofiejewa - Legeżyńska, Anna (Przegląd Rusycystyczny, 2020)
In different European cultures a word „devil” implies universal association with a concept of evil, sin and punishment. In my essay it is a metaphor of modern subject division. The devil in the form of alcohol steals consciousness from a person, a fight with evil ends in failure. The most prominent example of „alcohol prose” in Russian literature is Venedict Yerofeyev’s book Moscow-Petushki. For the first time it was available in Poland in 1976 thanks to “emigrant translation” (no censorship), then reprinted as an allegory of Soviet totalitarianism. Nowadays it requires new interpretation, therefore I choose new contexts and examples: a poem by Jerzy Liebert, pieces of prose by Malcolm Lowry (Under the Volcano), Marek Hłasko (Loop) and other Polish newest literary works. Analysing Russian narrative poem I pay attention to the problem of individual freedom in a desacralized world, where there are no moral values. I show a route of life-peregrination as a vicious circle that may be broken only by death. Character created by Yerofeyev is a person, who gave his “soul” (i.e. his identity) to the “devil”, but he did not made any choice, because he had been predestined to existence without consciousness.